First referral units (FRU): needs focus in Indian context - Pandve, Harshal T.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Health care delivery in India has been envisaged at three levels namely primary, secondary and tertiary. The secondary level of health care essentially includes Community Health Centres (CHCs), constituting the First Referral Units (FRUs) and the Sub-district and District Hospitals. The CHCs were designed to provide referral health care for cases from the Primary Health Centres level and for cases in need of specialist care approaching the centre directly. CHC is a 30-bedded hospital providing specialist care in Medicine, Obstetrics and Gynaecology, Surgery, Paediatrics, Dental and AYUSH. These centres are however fulfilling the tasks entrusted to them only to a limited extent. The launch of the National Rural Health Mission (NRHM) gives the opportunity to have a fresh look at their functioning. For the first time under National Rural Health Mission, an effort had been made to develop Indian Public Health Standards (IPHS) for a vast network of peripheral public health institutions in the country to provide optimal specialized care to the community and achieve and maintain an acceptable standard of quality of care.